The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2166/wst.2022.045
|View full text |Cite
|
Sign up to set email alerts
|

Startup and initial operation of an MLE-MABR treating municipal wastewater

Abstract: A 630 m3/d pilot plant was installed at Subiaco WRRF to determine design and operational parameters of a hybrid Modified Ludzack-Ettinger – Membrane Aerated Biofilm Reactor (MLE-MABR) configuration. Two commercial ZeeLung MABR cassettes were installed in series in the anoxic zone and the pilot was fed with primary effluent (averaging COD 601 mg/L, TKN 68.5 mg/L and 17–29 °C). A nitrifying biofilm was developed within 3 weeks and the nitrous oxide (N2O) gas emissions from the MABR exhaust gas proved to be a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although the improvements in NR observed in P2 in this study are still lower than previously reported for full-scale hybrid MABRs. Average values of NR of 2.1 g N m − 2 d − 1 [25] and 3.7 g N m − 2 d − 1 [69] have been recently reported in full-scale hybrid MABR experiences. This could be partially caused by the uncertainty in what was the exact NR occurring in the system, as previously discussed, but it could also have other potential causes.…”
Section: Nitrification Ratesmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the improvements in NR observed in P2 in this study are still lower than previously reported for full-scale hybrid MABRs. Average values of NR of 2.1 g N m − 2 d − 1 [25] and 3.7 g N m − 2 d − 1 [69] have been recently reported in full-scale hybrid MABR experiences. This could be partially caused by the uncertainty in what was the exact NR occurring in the system, as previously discussed, but it could also have other potential causes.…”
Section: Nitrification Ratesmentioning
confidence: 80%
“…Hydrodynamics can have a significant effect on biofilm activity. Indeed, [69] observed the highest NR when mixing was increased. In this study, R2 obtained the highest NR when the mixing was increased (P2b) and R1 when EA was the highest (P2).…”
Section: Nitrification Ratesmentioning
confidence: 95%
“…However, neither of those studies reported the N 2 O fraction that back-diffuses into the membrane lumen and could significantly change the final N 2 O emission mass balance. More recently, Silveira et al, 2022 showed that N 2 O concentrations measured in the MABR exhaust from a pilot treating 630 m 3 d − 1 were, on average, in the 60-120 ppm range and could be used to assess biofilm development during startup. This study, however, did not quantify the emission fraction coming from the bulk.…”
Section: Introductionmentioning
confidence: 99%